1998
DOI: 10.1210/en.139.3.1361
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Prolactin Promoter Activation in Individual Living Lactotrophic Cells

Abstract: The firefly luciferase gene has become widely used as a convenient reporter for studies of gene promoter regulation. Very recently, the development of ultralow-light imaging cameras has enabled the quantitative digital imaging of light signals resulting from luciferase activation in the presence of luciferin substrate. We have applied this technology to the study of PRL promoter activation in individual pituitary tumor cells to study the temporal and spatial characteristics of the expression of a well-characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 0 publications
7
44
0
Order By: Relevance
“…The firefly luciferase reporter gene has become widely used for assays of promoter function, and its activity can be monitored by microscopic luminescence imaging (White et al 1990, 1995, Craig et al 1991, Rutter et al 1998. Using real-time microscopic imaging of a stably transfected rat pituitary cell line, we have recently demonstrated that prolactin (PRL) promoter activity in individual living cells is not stable and exhibits unexpected 40-fold fluctuations from hour to hour (Takasuka et al 1998). Although different individual cells display markedly different mRNA content and peptide secretion rates as determined by in situ hybridization and haemolytic plaque assays (Hofland et al 1991), our data indicated that this heterogeneity is subject to rapid dynamic change (Takasuka et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The firefly luciferase reporter gene has become widely used for assays of promoter function, and its activity can be monitored by microscopic luminescence imaging (White et al 1990, 1995, Craig et al 1991, Rutter et al 1998. Using real-time microscopic imaging of a stably transfected rat pituitary cell line, we have recently demonstrated that prolactin (PRL) promoter activity in individual living cells is not stable and exhibits unexpected 40-fold fluctuations from hour to hour (Takasuka et al 1998). Although different individual cells display markedly different mRNA content and peptide secretion rates as determined by in situ hybridization and haemolytic plaque assays (Hofland et al 1991), our data indicated that this heterogeneity is subject to rapid dynamic change (Takasuka et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Using real-time microscopic imaging of a stably transfected rat pituitary cell line, we have recently demonstrated that prolactin (PRL) promoter activity in individual living cells is not stable and exhibits unexpected 40-fold fluctuations from hour to hour (Takasuka et al 1998). Although different individual cells display markedly different mRNA content and peptide secretion rates as determined by in situ hybridization and haemolytic plaque assays (Hofland et al 1991), our data indicated that this heterogeneity is subject to rapid dynamic change (Takasuka et al 1998). The mechanisms for the instability of PRL gene transcription are unknown, but recent imaging and biochemical data indicate that nuclear hormone receptors are recruited to and released from chromatin very rapidly in response to hormonal signals (McNally et al 2000, Shang et al 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these assays measure gene expression by extracting RNA from a population of cells, thus averaging gene expression across an entire population. Single-cell analysis using sophisticated microscopy has revealed startling heterogeneity of gene transcription between cells even within clonal populations (Takasuka et al 1998, Ashall et al 2009, Eldar & Elowitz 2010.† What kind of delivery system would be most appropriate (plasmid, viral, episomal, stably integrated or transient expression).…”
Section: Endogenous Versus Ectopic Gene Expressionmentioning
confidence: 99%
“…A pulse was defined as a significant rise in photonic activity corresponding to a value greater than 5 % of the photonic signal count at the beginning of the pulse plus two times the total signal-noise variation (SNV). SNV was calculated by the square root of each value plus the standard deviation (SD) of the corresponding background values squared (SNV = √[(signal count) + (SD of detected background 2 )]) (Takasuka et al, 1998). All the cells analyzed expressed a detectable level of luciferase activity (generating photonic patterns with or without pulses) that was significantly higher than the background level indicating that the cells remained viable during the course of the experiment.…”
Section: Bioluminescent Imaging Of Gnrh Gene Expression In Individualmentioning
confidence: 99%